Comparative endocrine disrupting effects of abamectin and indoxacarb insecticides - Nassar, Atef (International Journal of Pharmacology and Toxicology, 2016)
Abamectin and indoxacarb are relatively new insecticides with different mode of action and are applied to control a wide range of plant pests. However, their side effects to mammals are not fully studied. Accordingly, current study aimed to compare the adverse effects of both insecticides against the endocrine biomarkers: triiodothyronine (T3), tetraiodothyronine (T4), follicular-stimulating hormone (FSH), progesterone, and testosterone. These parameters were measured after orally-injecting rats with 1/20 LD50 doses of each of abamectin and indoxacarb for 60 days. Results showed that indoxacarb had pronounced reduction in the contents of T3 and FSH hormones compared to control and abamectin. Also, indoxacarb increased testosterone level compared to abamectin. T4 level was reduced by abamectin treatment compared to indoxacarb. Progesterone content was significantly increased after the abamectin treatment, while it was decreased after the indoxacarb treatment. However, the tested insecticides belong to avermectins and oxadiazine chemical groups that have different mode of action. They showed some similarity in their effect on T3, T4, and FSH, except for the progesterone hormone that showed a contradicting response. These two insecticides were marked as safe but current study highlight the need for caution during their application in the integrated pest management program.
Keywords: Insecticides; Avermectins; Oxadiazine; White Albino Rats; Endocrine Biomarkers.